Predominant Difficulties Encountered by English Department Student During the First Phase of Consecutive Interpreting - Farah Diba; Ahmad Jum’a Khatib Nur Ali (JEdu: Journal of English Education, 2023)
This objective of this research is to find out the predominant difficulties encountered by English department students during the first phase of consecutive interpreting. This research uses a descriptive qualitative method and conducted using the theory of Ribas (2012). The source of data of this research is BBC News video entitled “The Devastating Impact of War on the Lives of Ukraine’s Children”. The result of this research shows that lack of practice in listening is the predominant difficulty encountered by students. Whereas, the least difficulty encountered is lack of common sense. The message conveyed in the source language may be radically different for the listeners in the target language. Subsequently, interpreter encountered difficulties in attempting to create the equivalence. Therefore, it shows how much time is needed and it requires a certain amount of practice to be able to produce a good quality of interpretation.